Muslim by default or religious discrimination? Results from a~cross-national field experiment on hiring discrimination - Valentina Di Stasio; Bram Lancee; Susanne Veit; Ruta Yemane (Journal of Ethnic and Migration Studies, 2021)
We use data from a cross-nationally harmonised field experiment to examine discrimination towards Muslim job applicants in five European countries (Germany, the Netherlands, Norway, Spain and the United Kingdom). We focus on job applicants originating from countries that have a substantial Muslim population: of these, some signalled closeness to Islam in their job application while others did not. With this design, we can empirically disentangle anti-Muslim discrimination (a `disclosed Muslim' effect) from the possible stigma of originating from countries where Islam is prevalent (a `Muslim by default' effect). Our double-comparative design allows us to compare the extent of anti-Muslim discrimination faced by different origin groups in destination countries characterised by a varying history of church-state relations and distinctive approaches to grant cultural and religious rights to minorities. We find alarming levels of discrimination, especially towards male applicants from more visible groups. Anti-Muslim discrimination and origin-based discrimination independently contribute to the severe disadvantage faced by ethnic and religious minorities, a disadvantage that is especially severe in the Norwegian labour market.
Keywords: 330; field experiment; religious discrimination; Muslim; ethnic penalties; correspondence test